NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIADynamics of the troponin I levels in the first days after heart transplantation (HTX) in the own material – a pilot study - Wierzbicki, Karol; Sobczyk, Dorota; Milaniak, Irena; Bochenek, Maciej; Piątek, Jacek; Drwiła, Rafał; Kapelak, Bogusław; Krupa, Ferdynanda; Przybyłowski, Piotr; Ciołczyk-Wierzbicka, Dorota; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Troponin is a valuable and highly used marker for the assessment of the myocardial damage. Elevated troponin levels are the result of myocardial injury irrespective of etiology. Aim : Evaluation of dynamics of troponin I changes in the first days (since “0” to 3rd day) after heart transplantation (HTX). Material and methods : Retrospective analysis of 42 patients aged 21 to 62 years, average age 47.4 ±12.4. Study group consisted of the patients which hearts were harvested by two surgeons according to the identical protection scheme using CELSIOR cardioplegic solution. In all patients troponin I levels in the following days after HTX were measured. Dynamics of troponin I changes was assessed, using the one-step immunoenzymatic test (normal values to 0.1 ng/ml) in all of the patients in the first days after HTX. The highest daily value was taken into the analysis. Results : Average troponin I levels in the subsequent days after HTX were as follows: 21.7 ±22.1; 21.3 ±22.5; 17.6 ±20.3; 13.2 ±15.3 ng/ml. Based on ANOWA (Kruskal-Wallisa) test statistically significant troponin I levels decrease in the consecutive days after HTX (p = 0.0002) was noted. The biggest decrease was observed between days “0” and “3” and between days “1” and “3” (respectively: 54.1 and 53.7%); the smallest decreased appeared between days “0” and “1” after HTX (0.7%). Conclusion : Immediately after HTX significantly elevated troponin I levels can be observed that could be connected with perioperative myocardial injury caused by the heart harvesting and transplantation.